Morfología y distribución de Thysanophora crinita (Stylommatophora: Thysanophoridae) en Nicaragua - Mijail Pérez, A; Adolfo López, S J (Revista de Biología Tropical, 2002)
A morphological characterization of Thysanophora crinita (Fulton, 1916-1917), including a redescription of the shell and the first description of the genital system, the radula and the jaw, are made based on 58 living individuals and 1378 empty shells; the sample considered for biometry was of 81 specimens. Means and ranges were 3.51 mm (2.6-4.9) diameter and 2 mm (1.5-2.5) height. This species exhibits a discoidaldepressed shell, with an opaque hairy periostracum as its most remarkable feature. The genital system is typical of the genus, with a well developed penis and a pear-shaped bursa copulatrix. Jaw: 16 to 18 narrow plates and radula with 72 transversal rows, formula: (C/3 + 5L/2 + 6M/2) x 2. The Nicaraguan populations of T. crinita are very similar to T. crinita from Cartagena and T.c. arubana, and show dimensiones intermediate between both. This species was previously known from Carthagena, Colombia and is reported from Nicaragua for the first time. A distribution map is included.